1992
DOI: 10.1007/bf00114554
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic microbial metabolism of some alkylthiophenes found in petroleum

Abstract: Six alkylthiophenes, 2-hexadecyl-5-methylthiophene (I), 2-methyl-5-tridecylthiophene (II) and 2-butyl-5-tridecylthiophene (III), 2-(3,7-dimethyloctyl)-5-methylthiophene (IV), 2-methyl-5-(3,7,11,15-tetramethylhexadecyl)thiophene (V) and 2-ethyl-5-(3,7,11,15-tetramethylhexadecyl)thiophene (VI) were synthesized and used as substrates in biodegradation studies. The products of their aerobic metabolism by pure bacterial cultures were identified. In most cases, the long alkyl chains of these thiophenes were preferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
20
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 34 publications
(24 reference statements)
2
20
0
Order By: Relevance
“…In fungi (Beauveria, Penicillium, and Paecilomyces spp. ), both carboxylic acid and acetic acid derivatives accumulated from 2-n-dodecyltetrahydrothiophene (12). Similar phenomena have been observed in various microbial degradation processes of n-alkylcyclohexanes, n-alkylbenzenes, and nalkylbenzene sulfonic acids (3,11,20,23).…”
supporting
confidence: 74%
“…In fungi (Beauveria, Penicillium, and Paecilomyces spp. ), both carboxylic acid and acetic acid derivatives accumulated from 2-n-dodecyltetrahydrothiophene (12). Similar phenomena have been observed in various microbial degradation processes of n-alkylcyclohexanes, n-alkylbenzenes, and nalkylbenzene sulfonic acids (3,11,20,23).…”
supporting
confidence: 74%
“…The microbial metabolism of six alkylthiophenes was investigated previously (Fedorak & Peakman 1992). The compounds studied had a methyl, ethyl or butyl group in the 2-position of the thiophene ring, and side chains of 10 to 20 carbon atoms in the 5-position.…”
mentioning
confidence: 99%
“…With the exception of 2-(3,7-dimethyloctyl)-5-methylthiophene, the metabolites identified indicated that the long side chains were attacked by n-alkane-degrading bacteria. For example, 2-hexadecyl-5-methylthiophene was degraded to 5-methyl-2-thiophenecarboxylic acid and 5-methyl-2-thiopheneacetic acid that accumulated in cultures that contained no crude oil (Fedorak & Peakman 1992). However, these intermediates underwent further biotransformation to undetected metabolites if crude oil or n-hexadecane was added to the culture medium.…”
mentioning
confidence: 99%
See 2 more Smart Citations